Potential therapeutic targets of the JAK2/STAT3 signaling pathway in triple-negative breast cancer - Long, Lin; Fei, Xiangyu; Chen, Liucui; Yao, Liang; Lei, Xiaoyong (Frontiers in Oncology, 2024)
Triple-negative breast cancer (TNBC) poses a significant clinical challenge due to its propensity for metastasis and poor prognosis. TNBC evades the body's immune system recognition and attack through various mechanisms, including the Janus Kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) signaling pathway. This pathway, characterized by heightened activity in numerous solid tumors, exhibits pronounced activation in specific TNBC subtypes. Consequently, targeting the JAK2/STAT3 signaling pathway emerges as a promising and precise therapeutic strategy for TNBC. The signal transduction cascade of the JAK2/STAT3 pathway predominantly involves receptor tyrosine kinases, the tyrosine kinase JAK2, and the transcription factor STAT3. Ongoing preclinical studies and clinical research are actively investigating this pathway as a potential therapeutic target for TNBC treatment. This article comprehensively reviews preclinical and clinical investigations into TNBC treatment by targeting the JAK2/STAT3 signaling pathway using small molecule compounds. The review explores the role of the JAK2/STAT3 pathway in TNBC therapeutics, evaluating the benefits and limitations of active inhibitors and proteolysis-targeting chimeras in TNBC treatment. The aim is to facilitate the development of novel small-molecule compounds that target TNBC effectively. Ultimately, this work seeks to contribute to enhancing therapeutic efficacy for patients with TNBC.